2007
DOI: 10.5194/cp-3-683-2007
|View full text |Cite
|
Sign up to set email alerts
|

Information on the early Holocene climate constrains the summer sea ice projections for the 21st century

Abstract: Abstract. The summer sea ice extent strongly decreased in the Arctic over the last decades. This decline is very likely to continue in the future but uncertainty of projections is very large. An ensemble of experiments with the climate model LOVECLIM using 5 different parameter sets has been performed to show that summer sea ice changes during the early Holocene (8 kyr BP) and the 21st century are strongly linked, allowing for the reduction of this uncertainty. Using the limited number of records presently ava… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…2 W m −2 globally higher for 1976 to 2005 as compared to 1750) due to greenhouse-gas concentrations. Goosse et al (2007) found for LOVECLIM that the simulated sea-ice area fits reasonably well with modern-day observations. Our results confirm this, as we find that the simulated annual sea-ice area in our PRE2005 and 0kOG simulations (9.6 × 10 12 km 2 and 10.6 × 10 12 km 2 , respectively) agree well with observations (10.6 × 10 12 km 2 , cf.…”
Section: Modern Climatesupporting
confidence: 57%
“…2 W m −2 globally higher for 1976 to 2005 as compared to 1750) due to greenhouse-gas concentrations. Goosse et al (2007) found for LOVECLIM that the simulated sea-ice area fits reasonably well with modern-day observations. Our results confirm this, as we find that the simulated annual sea-ice area in our PRE2005 and 0kOG simulations (9.6 × 10 12 km 2 and 10.6 × 10 12 km 2 , respectively) agree well with observations (10.6 × 10 12 km 2 , cf.…”
Section: Modern Climatesupporting
confidence: 57%
“…The different simulations examined in this study were performed with LOVECLIM1.1 Goosse et al, 2007), a three-dimensional climate model of intermediate complexity which includes representations of the atmosphere, the ocean and sea ice, the terrestrial biosphere, the oceanic carbon cycle and the polar ice sheets. As the last two components were not activated in this study, they will not be described here.…”
Section: Model Description and Experimental Designmentioning
confidence: 99%
“…As has been suggested by Goosse et al (2007) one may obtain stronger response in the Arctic and smaller and thinner sea-ice covers if one considers the earlier part of the Holocene (around 9 to 8 ka BP) rather than the midHolocene. This may be a better period to use for investigation of the model response to the changes in solar insolation, since the orbital insolation forcing was stronger then.…”
Section: Discussionmentioning
confidence: 72%
“…5 are smaller for many of the models than the observed change in ice cover over the last 30 yr. Thus, it cannot be ruled out that internal model variability may obscure the response to the orbital forcing in some of the models with a weak response (Goosse et al, 2007).…”
Section: Discussionmentioning
confidence: 99%